2014
DOI: 10.1002/masy.201300225
|View full text |Cite
|
Sign up to set email alerts
|

Curaua Fibers/Epoxy Laminates with Improved Mechanical Properties: Effects of Fiber Treatment Conditions

Abstract: Summary: The use of lignocellulosic fibers as reinforcement in polymer composites has increased worldwide recently. Vegetal fibers have low cost and they are commonly available in Brazil. The curaua fibers in particular are of great importance for the development of the Amazon region. The mechanical behavior of the composites reinforced with fibers depends on the effectiveness of the transfer of the applied load by the matrix to the fibers, which is determined by the magnitude of the interfacial bonding betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…Other treatment of natural fiber involves the exposure in hot water at 80°C for 1h and then after both treatments dried in air for 48h. These procedures improve the mechanical interaction between hydrophobic epoxy resin and hydrophilic fibers, removing the waste components (lignin, hemicellulose) from the fibers [11][12][13][14] . The degradation of natural fiber is strongly connected with moisture and climatic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Other treatment of natural fiber involves the exposure in hot water at 80°C for 1h and then after both treatments dried in air for 48h. These procedures improve the mechanical interaction between hydrophobic epoxy resin and hydrophilic fibers, removing the waste components (lignin, hemicellulose) from the fibers [11][12][13][14] . The degradation of natural fiber is strongly connected with moisture and climatic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This is in accordance with what has been observed in literature that after certain time of treatment and for higher solution concentrations, the mechanical properties tend to decrease, showing the fiber is starting to erode. 3638 In Nam et al 36 it is also observed that the experiments on fiber with more than 72 h of treatment, result in lower tensile strength.…”
Section: Resultsmentioning
confidence: 97%
“…Still, there is some evidence of fiber pull-out, as pointed in Figure 10(a), indicating low adhesion with the polymeric matrix. 28
Figure 10.Scanning electron microscope images of tensile-fractures surfaces of composite samples with in natura (a), KOH-treated (b), and NaOH-treated (c) curaua fibers.
…”
Section: Resultsmentioning
confidence: 99%
“…Still, there is some evidence of fiber pull-out, as pointed in Figure 10(a), indicating low adhesion with the polymeric matrix. 28 Figures 10(b) and (c) exhibited the composites with treated fibers showed a higher degree of fibrillation, with greater evidence of fiber breakage rather than pull-out, ratifying the increase in reinforcement/matrix interaction. 11 Matrix cracking and fiber debonding were observed.…”
Section: Mechanical Properties and Fracture Morphology Of Composite L...mentioning
confidence: 87%